2005
DOI: 10.1016/j.jneuroim.2005.01.008
|View full text |Cite
|
Sign up to set email alerts
|

The immunomodulating neuropeptide alpha-melanocyte-stimulating hormone (α-MSH) suppresses LPS-stimulated TLR4 with IRAK-M in macrophages

Abstract: Since α-MSH suppresses endotoxin-induced inflammation by innate immunity, it is possible that α-MSH can suppress the interface between innate and adaptive immunity mediated by TLR4-stimulated macrophages. Endotoxin-stimulated macrophages treated with α-MSH are suppressed in nitric oxide and IL-12p70 production, and cannot enhance antigen-stimulated IFN-γ production by Th1 cells. In macrophages treated with α-MSH, the inhibitory molecule IRAK-M is bound to IRAK-1, the proximal intracellular signal molecule of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 51 publications
2
44
0
4
Order By: Relevance
“…It is interesting that in our study a-MSH did not significantly affect human DC maturation. This finding is supported by the recent study by Shen et al (12), who found, despite the previously well-documented inhibitory effects on murine macrophage function (26,27), that a-MSH and calcitonin gene-related peptide were not significantly inhibitory for murine DC. The finding that VIP similarly had no effect at physiological levels is perhaps to be expected since its main immunomodulatory effects are thought to be directed against T cells (28).…”
Section: Discussionsupporting
confidence: 69%
“…It is interesting that in our study a-MSH did not significantly affect human DC maturation. This finding is supported by the recent study by Shen et al (12), who found, despite the previously well-documented inhibitory effects on murine macrophage function (26,27), that a-MSH and calcitonin gene-related peptide were not significantly inhibitory for murine DC. The finding that VIP similarly had no effect at physiological levels is perhaps to be expected since its main immunomodulatory effects are thought to be directed against T cells (28).…”
Section: Discussionsupporting
confidence: 69%
“…In macrophages through the melanocortin 1 and 3 receptors, α-MSH suppresses the activation of NF-κB and p38MAP-kinase by IL-1, TNF-α, and endotoxin Manna and Aggarwal, 1998;Taherzadeh et al, 1999;Yoon et al, 2003). The α-MSH suppression of endotoxin mediated inflammation is the result of blocking toll like receptor-4 (TLR4) signaling in macrophages either through suppression of CD14 expression or by translocation of IRAK-M to the endotoxin-engaged TLR4 intracellular complex (Sarkar et al, 2003;Taylor, 2005). While α-MSH suppresses the activity of pro-inflammatory cytokines and cells, it can induce its own production and enhances its own receptor expression on macrophages potentially creating a selfperpetuating anti-inflammatory loop (Star et al, 1995;Taherzadeh et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…This inhibitory action, thought to be the main mechanism responsible for the antiinflammatory effects of melanocortins, appears to be mediated by cAMP production and PKA activation (Manna & Aggarwal, 1998). -MSH regulates NF-κB and also p38-MAPK pathways probably through a common upstream element by inducing the binding of the IL-1R-associated kinase 1 (IRAK 1) to its inhibitor IRAK-M in activated macrophages (Taylor, 2005). However, NF-B inhibition might not be the mechanism of action of melanocortins in all cell types studied.…”
Section: Mechanisms Of Anti-inflammatory Actions Of Melanocortinsmentioning
confidence: 95%
“…Beyond its many physiological roles, excessive NO production may be harmful and mediate tissue damage and cell death. Several studies indicate that melanocortin peptides exert a protective role by inhibiting iNOS expression in stimulated macrophages, thus leading to decreased NO production (Mandrika et al, 2001;Star et al, 1995;Taylor, 2005). PGs are a family of lipid molecules derived enzymatically from fatty acids with a broad spectrum of physiological functions.…”
Section: In Vitro Studiesmentioning
confidence: 99%